MANAJEMEN KELAS DALAM MENINGKATKAN EFEKTIFITAS PROSES BELAJAR MENGAJAR - Purnomo, Andri Cahyo (Jurnal Ilmiah Pendidikan dan Keislaman, 2022)
This study aims to determine classroom management in improving the effectiveness of the teaching and learning process. This research is a qualitative type through literature study. Literature study is another term for literature review, literature review, theoretical study, theoretical basis, literature review, and theoretical review. Class management in improving the effectiveness of teaching and learning can be known through an understanding of the concept of class management and the effectiveness of teaching and learning. The concept of class management can be seen in 1) the notion of class management; 2) class management factors; and 3) approach in classroom management. Meanwhile, to find out whether learning has been effective can be seen from a) the notion of effective learning; b) the characteristics of effective learning